Electron impact cross sections for H2, HD and D2. Issue 18 (January 2020) - Prajapati, D; Yadav, H; Vinodkumar, M; Vinodkumar, P C
Synopsis: The demand for electron-impact cross sections has increased tremendously in recent years. There is, however, a special interest in such cross sections for hydrogen molecules and its isotopomers, HD and D 2 . We have computed target properties & electron scattering cross sections for H 2, HD and D 2 and discuss different phenomena and their importance.